In Vitro Differentiation Potential of Human Placenta Derived Cells into Skin Cells - Ruhma Mahmood; Mahmood S. Choudhery; Azra Mehmood; Shaheen N. Khan; Sheikh Riazuddin (Stem Cells International)
Skin autografting is the most viable and aesthetic technique for treatment of extensive burns; however, this practice has potential limitations. Harvesting cells from neonatal sources (such as placental tissue) is a simple, inexpensive, and noninvasive procedure. In the current study authors sought to evaluate in vitro potential of human placenta derived stem cells to develop into skin-like cells. After extensive washing, amniotic membrane and umbilical cord tissue were separated to harvest amniotic epithelial cells (AECs) and umbilical cord mesenchymal stem cells (UC-MSCs), respectively. Both types of cells were characterized for the expression of embryonic lineage markers and their growth characteristics were determined. AECs and UC-MSCs were induced to differentiate into keratinocytes-like and dermal fibroblasts-like cells, respectively. After induction, morphological changes were detected by microscopy. The differentiation potential was further assessed using immunostaining and RT-PCR analyses. AECs were positive for cytokeratins and E-Cadherin while UC-MSCs were positive for fibroblast specific makers. AECs differentiated into keratinocytes-like cells showed positive expression of keratinocyte specific cytokeratins, involucrin, and loricrin. UC-MSCs differentiated into dermal fibroblast-like cells indicated expression of collagen type 3, desmin, FGF-7, fibroblast activation protein alpha, procollagen-1, and vimentin. In conclusion, placenta is a potential source of cells to develop into skin-like cells.